1995
DOI: 10.1007/bf01991779
|View full text |Cite
|
Sign up to set email alerts
|

An international perspective on the prevalence of the Wernicke-Korsakoff syndrome

Abstract: In the Western world previous studies have shown that the majority of cases of the Wernicke-Korsakoff syndrome (WKS), which is caused by thiamine deficiency, occur in alcoholics. However, in France, a country with one of the highest per capita consumptions of alcohol, the prevalence of the WKS was found to be only 0.4% in a small retrospective autopsy study. This figure is compared with data sent to the authors by a number of neuropathologists from the U.S.A., Europe, Scandinavia and Australia. There was no ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 15 publications
1
50
0
4
Order By: Relevance
“…Even though the per capita wine consumption in France is nearly double than that in Australia, the incidence of the alcohol-related neurological complication of Wernicke-Korsakoff 's disease is significantly lower in France than in Australia. 3,4 The question of how much alcohol is safe has come into focus again since several recent studies have demonstrated modest cardiovascular benefits associated with light to moderate alcohol consumption. 5 Because alcohol use is often associated with both high-risk sexual behaviors and injection drug use, two of the main routes of HIV (human immunodeficiency virus) transmission, there is some evidence that suggest that individuals who abuse alcohol may be more likely to become HIV-infected than those who do not.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the per capita wine consumption in France is nearly double than that in Australia, the incidence of the alcohol-related neurological complication of Wernicke-Korsakoff 's disease is significantly lower in France than in Australia. 3,4 The question of how much alcohol is safe has come into focus again since several recent studies have demonstrated modest cardiovascular benefits associated with light to moderate alcohol consumption. 5 Because alcohol use is often associated with both high-risk sexual behaviors and injection drug use, two of the main routes of HIV (human immunodeficiency virus) transmission, there is some evidence that suggest that individuals who abuse alcohol may be more likely to become HIV-infected than those who do not.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroradiological studies of WE since the 1970s report in vivo signs of hyperintensity in thalamus, periventricular gray matter, inferior colliculi, and occasionally in cerebellum, observations consistent with post-mortem reports (eg, Baker et al, 1999;Kril, 1988, 1990;Kril et al, 1997;Torvik et al, 1982Torvik et al, , 1986, with partial lesion resolution with treatment. Given the wide variety of precipitating conditions and the devastating morbidities and premature mortality associated with this treatable condition (cf, Harper and Butterworth, 1997;Harper et al, 1995Harper et al, , 1998, it remains clinically relevant to have the means to identify the neuroradiological signature of thiamine deficiency in an animal model of WE with a known etiology and to track the brain lesion for neuronal damage and treatment-associated recovery, as is possible with quantitative in vivo magnetic resonance spectroscopy (MRS).…”
Section: Introductionmentioning
confidence: 99%
“…3 The prevalence of Wernicke-Korsakoff syndrome is estimated to be 1-2% in the general population and may be higher, between 12.5 and 35% in people with alcohol dependence. 1,2,4,5 Indirect evidence is available to indicate that Wernicke's encephalopathy is underrecognised and, consequently, undertreated. Studies point to an ante mortem diagnosis of Wernicke's encephalopathy in only 5-14% of patients.…”
mentioning
confidence: 99%